2018
DOI: 10.2106/jbjs.17.00279
|View full text |Cite|
|
Sign up to set email alerts
|

State Variation in Medicaid Reimbursements for Orthopaedic Surgery

Abstract: Variability of Medicaid reimbursement for inpatient orthopaedic procedures among states is substantial. This variation becomes especially remarkable given recent policy shifts toward focusing reimbursements on value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Prior studies described similar variability that exists among general orthopedics and its subspecialties. Lalezari et al 9 studied the 10 most commonly performed inpatient orthopedic procedures and found a great magnitude of variation between MCD and MCR reimbursement with coefficients of variations ranging from 0.32 in hip hemiarthroplasty to 0.57 in posterolateral lumbar interbody arthrodesis. Of note, the range of variability of MCD reimbursement was greater than $1500 for all procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies described similar variability that exists among general orthopedics and its subspecialties. Lalezari et al 9 studied the 10 most commonly performed inpatient orthopedic procedures and found a great magnitude of variation between MCD and MCR reimbursement with coefficients of variations ranging from 0.32 in hip hemiarthroplasty to 0.57 in posterolateral lumbar interbody arthrodesis. Of note, the range of variability of MCD reimbursement was greater than $1500 for all procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Using the methodology of Lalezari et al, 9 the Medicare Wage Index was calculated to adjust for cost of living in different states to create an MCR Wage Index-Adjusted MCD reimbursement. The range of variation in MCD reimbursement and MCR Wage Index-adjusted MCD reimbursement was described, as well as the coefficient of variation (standard deviation divided by mean).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each category of admissions (all cases, elective, and trauma), the number of admissions in the category was used as the weighting variable. Forms of the coefficient of variation have been used in prior orthopaedic health services work to quantify variation [13][14][15][16][17] , with values of >60 being considered very high variation 16,17 .…”
Section: Methodsmentioning
confidence: 99%